Teaching procedural justice and communication skills during police–community encounters: Results of a randomized control trial with police recruits - Rosenbaum, Dennis P. (Journal of experimental criminology, 2017)
To describe and evaluate Chicago’s Quality Interaction Program (QIP) for police recruits. The training focused on procedural justice, interpersonal communication, decision-making, cultural awareness, and stress management during encounters with the public. Attention was given to emotions, empathy, and communication skills.